Methodological basis of forming the nterethnic tolerance among youth in the multicultural environment of Kazakhstan and Belarus - G. Gainutdinova, Alsu (2018)
Article is devoted to the research of the problem of interethnic tolerance, activity of ethno-cultural associations, directed to formation of interethnic tolerance among youth in the conditions of the multicultural environment. There were analyzed the theoretical and methodological approaches to the problem of interethnic tolerance in foreign practice, the regularities and principles of functioning of ethnocultural associations as forms of social and cultural activity of youth in the conditions of the Republic of Belarus, the mechanisms of educative impact of the multicultural environment on process of formation of interethnic tolerance among youth on the example of the Republic of Kazakhstan. Special attention is paid to the study of new educational strategies and approaches on formation of interethnic tolerance among youth in the sphere of culture where the specificity of the Kazakhstan-Belarusian experience of the organization of this socially important segment of educational services can be useful to other countries as well. The materials of scientific publications and applied researches of authors in the field of education were used for achievement of the purpose of work. Based on the conducted research, the article proposes scientifically based conclusions and recommendations on the organization of process of formation of interethnic tolerance among youth in the conditions of the multicultural environment.